THE ROLE OF SD NEGERI 102052 BAGAN KUALA TEACHERS IN SHAPING STUDENT CHARACTER DURING THE COVID-19 PANDEMIC. - Andini Arafah; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
The study was entitled country primary school teachers role 105052 Bagan Kuala chart in creating student characters during the covid-19 pandemic. The problem arose was the difficulty of teachers forming the school's character in the new normal era and also the difficulty of understanding the language of the students in the village. The teacher's role asa learner is a role associated with the duties of providing assistance, supervision and coaching and discipline of learners. The role of teachers in today's modern education is increasingly complex, not only as a teacher but also as a person who shapes character, morals, and culture for learners. In the covid-19 era this education of children's character was out of control because school was not fully equipped to carry out the normal activities.The purpose of this study is to address the teacher's role in shaping the character of the students at the time of the current pandemic through long-distance schools while learners are studying online from home. The study USES a qualitative descriptive approach of library and objective studies teachers in the chart of Bagan Kuala. With this method of research I hope to bring about a change in the normal character of new scholars. Keywords: role of teacher, character, pandemic ________________________________________